2003
DOI: 10.1152/ajpheart.00932.2001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ca2+/calmodulin-dependent protein kinase II in endothelial NO production and endothelium-dependent relaxation

Abstract: Nitric oxide (NO) is synthesized from l-arginine by the Ca(2+)/calmodulin-sensitive endothelial NO synthase (NOS) isoform (eNOS). The present study assesses the role of Ca(2+)/calmodulin-dependent protein kinase II (CaMK II) in endothelium-dependent relaxation and NO synthesis. The effects of three CaMK II inhibitors were investigated in endothelium-intact aortic rings of normotensive rats. NO synthesis was assessed by a NO sensor and chemiluminescence in culture medium of cultured porcine aortic endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 47 publications
5
69
1
Order By: Relevance
“…This increase would in turn lead to an increase in the intestinal absorption of calcium, which may result in increased intracellular calcium, which would in turn stimulate the production of NO, a potent vasodilator purported to have protective effects on the endothelium. This is an indirect route by which vitamin D increases nitric oxide availability [46]. renin suppression, independent of calcium metabolism [48].…”
Section: Discussionmentioning
confidence: 99%
“…This increase would in turn lead to an increase in the intestinal absorption of calcium, which may result in increased intracellular calcium, which would in turn stimulate the production of NO, a potent vasodilator purported to have protective effects on the endothelium. This is an indirect route by which vitamin D increases nitric oxide availability [46]. renin suppression, independent of calcium metabolism [48].…”
Section: Discussionmentioning
confidence: 99%
“…Several kinases share the ability to phosphorylate this site, including protein kinase A, protein kinase C, CAMKII and the serine/threonine kinase AKT. [7][8][9][10][11] This latter seems to possess the unique feature to be activated by many independent signal transduction pathways. In fact, AKT kinase is activated primarily in response to stimulation of transmembrane receptors with intrinsic tyrosine kinase activity or indirectly coupled to tyrosine kinases or to 7-transmembrane G protein-coupled receptors.…”
mentioning
confidence: 99%
“…Hence, the activation observed upon eNOS phosphorylation on Ser1179 very likely reflects the displacement of this a-helix and the concomitant increased electron transfer within the reductase domain. In addition, eNOS Ser1179 phosphorylation (very frequently accompanied by coordinated dephosphorylation of Thr495) diminishes the Ca 2+ sensitivity of the enzyme (Fulton et al, 1999;McCabe et al, 2000;Schneider et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Upon the application of fluid shear stress (Dimmeler et al, 1999;Gallis et al, 1999), acute mechanical stretch (Hu et al, 2013) or UV light (Park et al, 2011), eNOS becomes rapidly phosphorylated on Ser1179. Likewise, treatment of endothelial monolayers with VEGF (Fulton et al, 1999;Michell et al, 1999), insulin (Salt et al, 2003), estrogens (Haynes et al, 2000), endothelin-1 (Liu et al, 2003) or bradykinin (Fleming et al, 2001;Schneider et al, 2003) leads to eNOS Ser1179 phosphorylation. To date, it has been shown that at least six protein kinases [Akt, AMPK, PKA, cGK-I/PKG, Chk1 and Ca 2+ / calmodulin-dependent protein kinase II (CaMKII)] are involved in Fig.…”
Section: Discussionmentioning
confidence: 99%